A pilot study exploring the molecular architecture of the tumor microenvironment in human prostate cancer using laser capture microdissection and reverse phase protein microarray. Issue 10 (14th October 2016) - Pin, Elisa; Stratton, Steven; Belluco, Claudio; Liotta, Lance; Nagle, Ray; Hodge, K. Alex; Deng, Jianghong; Dong, Ting; Baldelli, Elisa; Petricoin, Emanuel; Pierobon, Mariaelena
Abstract: The cross‐talk between tumor epithelium and surrounding stromal/immune microenvironment is essential to sustain tumor growth and progression and provides new opportunities for the development of targeted treatments focused on disrupting the tumor ecology. Identification of novel approaches to study these interactions is of primary importance. Using laser capture microdissection (LCM) coupled with reverse phase protein microarray (RPPA) based protein signaling activation mapping we explored the molecular interconnection between tumor epithelium and surrounding stromal microenvironment in 18 prostate cancer (PCa) specimens. Four specimen‐matched cellular compartments (normal‐appearing epithelium and its adjacent stroma, and malignant epithelium and its adjacent stroma) were isolated for each case. The signaling network analysis of the four compartments unraveled a number of molecular mechanisms underlying the communication between tumor cells and stroma in the context of the tumor microenvironment. In particular, differential expression of inflammatory mediators like IL‐8 and IL‐10 by the stroma cells appeared to modulate specific cross‐talks between the tumor cells and surrounding microenvironment. Highlights: LCM allows to isolate multiple cellular compartments from the same biological specimen. LCM coupled with RPPA are suitable for evaluating the cross‐talk between tumor and stroma. Stroma and epithelium profiling unravel the molecular base of cellular communication.